The concept of the level of computerization evaluation with respect to process management maturity building in local governments - Flieger, Michał; Chomiak-Orsa, Iwona (Koncepcja oceny poziomu informatyzacji w osiąganiu dojrzałości procesowej w urzędach gmin, 2012)
In contemporary conditions, organizations look for ways of achieving a competitive advantage in all possible areas. Recently they have turned to improving their managements systems. One possible change is moving away from traditional structures and turning them into processes due to the introduction of process management. In the article the authors have shown the stages through which local governments must move to achieve a full level of process maturity. Special research has been conducted to establish how many local governments in Lower Silesian Viovodeship have introduced fully process management. Also, the research has enabled us to get to know on what level of computerization the local governments are and what technologies they use. Moreover, the use of BPM instruments has been examined. The research has shown that local governments in that region are not advanced in terms of process management practices and technologies in use
Informatyka Ekonomiczna = Business Informatics, 2012, Nr 2 (24), s. 23-32
Keywords: computerization; evaluation of computerization; local government unit management; process development levels; informatyzacja; ocena poziomu informatyzacji; zarządzanie w urzędach gmin; poziomy zarządzania procesowego